Graphite composite material and preparation method and application thereof

By covering the graphite composite with a composite porous carbon layer on the graphite surface, the problems of slow charging speed and reduced circulation performance of artificial graphite materials during fast charging and long circulation use are solved, and the battery performance with efficient fast charging and long life is achieved .

CN119480988APending Publication Date: 2025-02-18ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411610967.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing artificial graphite materials have problems of slow charging speed and degradation of cycle performance during fast charging and long circulation use, making it difficult to find a balance between fast charging performance and cycle stability.

Method used

The graphite composite material is used to coat the composite porous carbon layer on the graphite surface. The composite porous carbon layer combines the advantages of hard carbon and graphitized carbon. By adjusting the mass ratio of the cladding raw materials, the thickness and pore size distribution of the cladding layer are controlled. .

Benefits of technology

It significantly improves the transmission efficiency of lithium ions, enhances the structural stability of the material, improves the fast charging performance and cycle stability of the battery, extends the service life, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480988A_ABST
    Figure CN119480988A_ABST
Patent Text Reader

Abstract

The invention discloses a graphite composite material as well as a preparation method and application thereof. The material comprises graphite and a composite porous carbon layer coating the graphite, the composite porous carbon layer contains hard carbon and graphitized carbon, the graphite composite material is prepared from the raw materials of the composite porous carbon layer, the graphite and an oxygen-containing pore-forming agent, the raw materials of the composite porous carbon layer comprise a hard carbon precursor and a graphitized carbon precursor, and the oxygen-containing pore-forming agent is prepared from the hard carbon precursor and the graphitized carbon precursor. The mass ratio of the graphite to the total mass of the raw materials of the composite porous carbon layer is less than 28: 1, and the mass ratio of the graphitized carbon precursor to the hard carbon precursor is more than 1: 1; the ratio of the total mass of the raw materials of the composite porous carbon layer to the mass of the oxygen-containing pore-forming agent is more than 10: 1. When the graphite composite material disclosed by the invention is prepared into a negative electrode material of a secondary battery, the graphite composite material has excellent quick charging performance and good cycling stability, and a new possibility is developed for high-performance battery application in multiple fields of electric automobiles, portable electronic equipment, energy storage systems and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to secondary batteries, and in particular to a graphite composite material and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of science and technology, the negative electrode material system of traditional secondary batteries, especially lithium-ion batteries, is becoming increasingly rich, among which graphite materials (such as natural graphite and artificial synthetic graphite) and amorphous carbon materials constitute its important cornerstone. Particularly noteworthy is that artificial graphite materials have firmly occupied the dominant position in the lithium-ion battery negative electrode material market since their commercial application in 1993 due to their cost-effectiveness, stable electrochemical properties and high safety. After more than 30 years of technological iteration and innovation, the theoretical capacity of artificial graphite materials is now close to its physical limit, about 360mAh / g, and the annual market demand is as high as one million tons, demonstrating its huge potential and wide application scenarios in the field of energy storage.

[0003] However, even as a mainstream material, the challenges of artificial graphite in the era of fast charging cannot be ignored. Its core defects lie in its inherent surface structure and micromorphology: the anisotropy of the surface structure limits the number of active sites for lithium ion embedding, making it difficult for lithium ions to migrate quickly and effectively between graphite layers during high-rate charging, thus affecting the charging speed; at the same time, the narrow interlayer spacing further hinders the rapid diffusion of lithium ions, exacerbating the limitation of fast charging performance.

[0004] In response to this bottleneck, the scientific research community has actively explored and practiced a variety of strategies, such as fine-tuning particle size, surface coating or doping modification, in order to maintain or enhance cycle stability while improving fast charging performance. Although these methods have improved the charging performance of artificial graphite to a certain extent, such as the Chinese patent application document CN117393737A discloses a nitrogen-doped carbon-coated graphite negative electrode material and its preparation method, application, and battery, specifically disclosing that through nitrogen-doped carbon coating technology, a significant improvement in fast charging performance is achieved under certain conditions (such as a capacity of 72.3% at a 1C rate of 0.1C), but the resulting decrease in cycle performance (such as a capacity retention rate of only 92.1% after 500 cycles under 1C / 1C conditions) is still a problem that needs to be solved.

[0005] In view of this, the development of a new graphite negative electrode material that can break through the limitations of traditional artificial graphite negative electrode materials while finding a better balance between fast charging performance and cycle stability will have good application prospects. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a graphite composite material, and a secondary battery prepared from the material has good fast charging performance and cycle stability.

[0007] The invention also provides a method for preparing the material.

[0008] The present invention also proposes the application of the above material.

[0009] According to the first aspect of the present invention, the graphite composite material comprises graphite and a composite porous carbon layer coated on the graphite, the composite porous carbon layer comprises hard carbon and graphitized carbon, the raw materials for preparing the graphite composite material comprise composite porous carbon layer raw material, graphite and oxygen-containing pore-forming agent, the composite porous carbon layer raw material comprises a hard carbon precursor and a graphitized carbon precursor, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is less than 28:1, the ratio of the mass of the hard carbon precursor to the graphitized carbon precursor is less than 1:1; the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is less than 150:1.

[0010] According to the graphite composite material of the embodiment of the present invention, at least the following beneficial effects are achieved: the present invention creatively proposes a new type of graphite composite material, which is coated with a composite porous carbon layer on the surface of the graphite core, and the composite porous carbon layer cleverly combines the respective advantages of hard carbon and graphitized carbon: the hard carbon part, with its difficult graphitization characteristics, exhibits excellent lithium ion diffusion ability and outstanding mechanical stability. This characteristic significantly improves the transmission efficiency of lithium ions during the charging process, significantly inhibits the formation and precipitation of lithium dendrites, thereby enhancing the structural stability of the material, reducing the structural damage of the negative electrode material of the battery during repeated charge and discharge cycles, thereby improving the safety performance of the battery and extending its service life. On the other hand, the graphitized carbon part in the composite layer, with its excellent electronic conductivity and ordered carbon layer structure, not only promotes the rapid transmission of electrons inside the material, but also accelerates the diffusion process of lithium ions, and effectively alleviates the expansion and contraction of the graphite volume during the charge and discharge process, significantly optimizing the electrochemical properties of the material. In addition, the design of the composite porous carbon layer also introduces a rich pore structure. These pores not only provide more active sites for the embedding and extraction of lithium ions, but also greatly shorten the diffusion path of lithium ions, further improving the material's fast charging capability and cycle stability, and effectively overcoming the performance bottleneck faced by traditional graphite negative electrode materials during fast charging and long-cycle use.

[0011] By adjusting the mass ratio of the coating layer raw material (i.e., the composite porous carbon layer raw material) to the graphite and pore-forming agent, controlling the thickness and pore size distribution of the coating layer, and controlling its mass ratio within the scope of the present invention, the graphite composite material of the present invention can be made to have excellent fast charging performance and good cycle stability when prepared as a negative electrode material for a secondary battery. It can not only ensure that the battery is charged in a very short time, meeting the urgent needs of modern society for efficient energy storage, but also effectively suppress the attenuation of battery performance with the number of cycles, and realize the long-life operation of the battery. In addition, the material also takes into account the safety of the battery during use, provides important technical support for the development of high-performance secondary batteries in the future, meets the market's high standards for fast charging, long life and safety, and opens up new possibilities for the application of high-performance batteries in multiple fields such as electric vehicles, portable electronic devices, and energy storage systems.

[0012] According to some embodiments of the present invention, the composite porous carbon layer contains a plurality of macropores. The carbon coating layer on the surface of the composite porous carbon layer-coated graphite negative electrode material provided by the present invention contains a large number of macropores. These macropores can effectively improve the wettability of the electrolyte during the lithium insertion process of the material, and provide channels for lithium ion insertion, and the lithium ion diffusion performance of the material is better. The macroporous structure can increase the specific surface area of ​​the material and provide more active sites for lithium insertion, which is beneficial to the charge transfer of lithium ions on the surface of the material.

[0013] According to some embodiments of the present invention, the average pore diameter of the composite porous carbon layer is 15-100 nm.

[0014] According to some embodiments of the present invention, the average pore diameter of the composite porous carbon layer is 50-100 nm.

[0015] According to some embodiments of the present invention, the average pore diameter of the composite porous carbon layer is 60-90 nm.

[0016] According to some embodiments of the present invention, the average pore diameter of the composite porous carbon layer is 70-90 nm.

[0017] According to some embodiments of the present invention, the specific surface area of ​​the composite porous carbon layer is 0.5 to 3.0 m 2 / g.

[0018] According to some embodiments of the present invention, the specific surface area of ​​the composite porous carbon layer is 0.7 to 2.2 m 2 / g.

[0019] According to some embodiments of the present invention, the porosity of the composite porous carbon layer is above 2%. The high porosity of the composite porous carbon layer makes the porous carbon layer-coated graphite negative electrode material have excellent fast charging performance.

[0020] According to some embodiments of the present invention, the porosity of the composite porous carbon layer is above 2 to 9%.

[0021] The size and distribution density of pores in the composite porous carbon layer have significant and complex effects on the diffusion kinetics and overall performance of lithium ions in graphite negative electrode materials. Specifically, increasing the pore size can provide more spacious embedding channels for lithium ions, which can accelerate the diffusion rate of lithium ions to a certain extent, especially during fast charging. However, large pores also mean that a higher specific surface area is exposed to the electrolyte, thereby increasing the possibility of side reactions between graphite particles and the electrolyte. These side reactions, such as the repeated formation and rupture of the solid electrolyte interface film (SEI) and the decomposition of the electrolyte, not only consume active lithium and electrolyte, but also may cause structural damage to the surface of graphite particles, thereby affecting the cycle stability of the material. Therefore, fine-tuning the size and distribution of pores can better achieve the dual goals of rapid lithium ion diffusion and good cycle stability.

[0022] According to some embodiments of the present invention, the composite porous carbon layer has a thickness of 20 to 200 nm.

[0023] According to some embodiments of the present invention, the composite porous carbon layer has a thickness of 50 to 150 nm.

[0024] According to some embodiments of the present invention, the composite porous carbon layer has a thickness of 50 to 80 nm.

[0025] The thickness of the composite porous carbon layer affects both the fast charging performance and the cycle performance of the composite porous carbon layer-coated graphite negative electrode material. When it is too thin, although the fast electron transport capability of the graphite core may be maintained to a certain extent, the number of active lithium insertion sites on the surface of the graphite negative electrode material is relatively reduced due to the limited surface area, which limits the rapid insertion and diffusion of lithium ions during the charging process, thereby reducing the fast charging performance of the material. In addition, the thinner carbon layer may not provide sufficient mechanical support and protection for the graphite core, making the negative electrode material more susceptible to electrolyte erosion during the cycle, thereby exacerbating the decline in cycle performance. When it is thicker, although the number of active lithium insertion sites on the surface of the material is increased, which helps to improve the fast charging performance, it also significantly increases the contact area between the graphite negative electrode material and the electrolyte. This increased contact area provides more opportunities for side reactions in the electrolyte, such as the unstable growth of the solid electrolyte interface film (SEI) and the continuous decomposition of the electrolyte. These side reactions not only consume active lithium and electrolyte, but may also cause the destruction of the structure of the negative electrode material, thereby seriously affecting the cycle stability of the battery.

[0026] Therefore, in order to achieve a good balance between fast charging performance and cycle performance, the thickness of the composite porous carbon layer needs to be carefully controlled. The ideal porous carbon layer thickness should be able to provide sufficient active lithium insertion sites to support fast charging, and effectively inhibit the occurrence of side reactions and protect the graphite core from electrolyte corrosion, thereby ensuring that the negative electrode material maintains stable electrochemical performance during long-term use.

[0027] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 1:1 to 10:1, such as 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1.

[0028] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 4:1 to 6:1. Graphitized carbon has a stable crystal structure, and is not easily damaged by its own volume change during the lithium insertion and extraction process of the material, and has better cycle stability. The hard carbon structure has a large number of active sites on the surface for lithium ion embedding, which can effectively reduce the charge transfer impedance of graphite and has better fast charging performance.

[0029] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 5:1.

[0030] According to some embodiments of the present invention, the hard carbon precursor includes at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose, and polyvinyl pyrrolidone.

[0031] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 25:1.

[0032] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 20:1.

[0033] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 15:1.

[0034] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 10:1.

[0035] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 9:1.

[0036] According to some embodiments of the present invention, the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 10: 1 to 100: 1. During the preparation of the graphite composite material of the present invention, the pore size of the coating layer can be adjusted by adjusting the mixing ratio of the oxygen-containing pore-forming agent.

[0037] According to some embodiments of the present invention, the mass ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 40:1 to 60:1.

[0038] According to some embodiments of the present invention, the mass ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 50:1.

[0039] According to some embodiments of the present invention, the graphitized carbon precursor is asphalt. Asphalt pyrolysis carbon belongs to the soft carbon category, which will gradually graphitize at a high temperature of more than 2600°C and belongs to an easily graphitized carbon material. Hard carbon belongs to a difficult-to-graphitize carbon material and is not easily graphitized at a high temperature of more than 2600°C. The coating layer of the composite porous carbon layer coated with graphite provided by the present invention contains both graphitized carbon and hard carbon, and can have both the high stability of graphitized carbon and the high lithium ion diffusivity of hard carbon.

[0040] According to some embodiments of the present invention, the graphitized carbon precursor includes at least one of coal tar pitch, petroleum pitch and natural pitch.

[0041] According to some embodiments of the present invention, the oxygen-containing pore former includes phosphorus pentoxide. In the present invention, oxygen-containing pore formers such as phosphorus pentoxide are introduced into the carbon coating process, and the oxygen-containing pore former and the carbon coating layer undergo an oxidation reaction at high temperature to form dense and uniform macropores in the carbon coating layer, providing more channels for lithium ion embedding, while generating a larger specific surface area, and the lithium embedding active sites on the surface of the material are also increased accordingly, further improving the fast charging performance of the material.

[0042] The preparation method according to the second aspect of the present invention comprises the following steps:

[0043] S1, mixing the composite porous carbon layer raw material with graphite and an oxygen-containing pore-forming agent, and heating them to obtain pre-coated graphite;

[0044] S2, graphitizing the pre-coated graphite under an inert atmosphere to obtain the graphite composite material;

[0045] Among them, the composite porous carbon layer raw material includes a hard carbon precursor and a graphitized carbon precursor, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is less than 28:1, and the mass ratio of the graphitized carbon precursor to the hard carbon precursor is greater than 1:1; the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is greater than 10:1.

[0046] The preparation method according to the embodiment of the present invention has at least the following beneficial effects: the scheme of the present invention uses a composite porous carbon layer raw material containing a hard carbon precursor and a graphitized carbon precursor to coat hard carbon and graphitized carbon on the surface of graphite, and uses the hard carbon and graphitized carbon coating combined with pore making to prepare a high-porosity hard carbon composite graphitized carbon-coated graphite negative electrode material, which has strong structural stability, excellent electronic conductivity and lithium ion diffusion performance, and can effectively solve the problems of fast charging and poor cycle performance when the existing graphite material is used as a negative electrode material. By adjusting the mass ratio of the coating layer raw material (i.e., the composite porous carbon layer raw material) to the graphite and the pore-forming agent, the thickness and pore size distribution of the coating layer can be effectively controlled, and the operation is simple. By controlling the above parameters, it not only avoids the lack of active lithium insertion sites caused by the coating layer being too thin, but also overcomes the problem of limiting the diffusion rate of lithium ions due to the small pore size. This precise control mechanism ensures that the prepared graphite negative electrode material can surpass the level of existing graphite materials in fast charging performance, cycle stability and overall electrochemical performance, providing strong material support for the development and application of high-performance lithium-ion batteries.

[0047] According to some embodiments of the present invention, the pre-coating treatment temperature is lower than 500°C.

[0048] According to some embodiments of the present invention, the pre-coating treatment temperature is 200-400°C.

[0049] According to some embodiments of the present invention, the pre-coating treatment temperature is 300-350°C.

[0050] According to some embodiments of the present invention, the pre-coating treatment time is 1 to 3 hours.

[0051] According to some embodiments of the present invention, the pre-coating treatment time is 1.5 to 2.5 hours.

[0052] According to some embodiments of the present invention, the pre-coating treatment time is 2 hours.

[0053] According to some embodiments of the present invention, the pre-coating is performed in a coating machine.

[0054] According to some embodiments of the present invention, the coating machine includes one of a vertical kettle, a horizontal kettle, a drum furnace, and a melting machine.

[0055] According to some embodiments of the present invention, step S1 further comprises the step of subjecting the composite porous carbon layer raw material containing the hard carbon precursor and the graphitized carbon precursor to high-speed shear grinding.

[0056] According to some embodiments of the present invention, the rotation speed during the high-speed shear grinding process is 10000 rpm to 30000 rpm.

[0057] According to some embodiments of the present invention, the rotation speed during the high-speed shear grinding process is 15000 rpm to 20000 rpm.

[0058] According to some embodiments of the present invention, the rotation speed during the high-speed shear grinding process is 15500-16500 rpm, such as 16000 rpm.

[0059] According to some embodiments of the present invention, the inert atmosphere includes at least one of a nitrogen atmosphere or an inert gas atmosphere, such as nitrogen, helium or argon.

[0060] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 1:1 to 10:1.

[0061] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 4:1 to 6:1.

[0062] According to some embodiments of the present invention, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is 5:1.

[0063] According to some embodiments of the present invention, the hard carbon precursor includes at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose, and polyvinyl pyrrolidone.

[0064] According to some embodiments of the present invention, the graphitized carbon precursor is asphalt. Asphalt pyrolysis carbon belongs to the soft carbon category, which will gradually graphitize at a high temperature of more than 2600°C and belongs to an easily graphitized carbon material. Hard carbon belongs to a difficult-to-graphitize carbon material and is not easily graphitized at a high temperature of more than 2600°C. The coating layer of the composite porous carbon layer coated with graphite provided by the present invention contains both graphitized carbon and hard carbon, and can have both the high stability of graphitized carbon and the high lithium ion diffusivity of hard carbon.

[0065] According to some embodiments of the present invention, the graphitized carbon precursor includes at least one of coal tar pitch, petroleum pitch and natural pitch.

[0066] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 25:1.

[0067] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 20:1.

[0068] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 15:1.

[0069] According to some embodiments of the present invention, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 10:1.

[0070] According to some embodiments of the present invention, the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 10: 1 to 100: 1. During the preparation of the graphite composite material of the present invention, the pore size of the coating layer can be adjusted by adjusting the mixing ratio of the oxygen-containing pore-forming agent.

[0071] According to some embodiments of the present invention, the mass ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 40:1 to 60:1.

[0072] According to some embodiments of the present invention, the mass ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 50:1.

[0073] According to some embodiments of the present invention, the oxygen-containing pore former includes phosphorus pentoxide. In the present invention, oxygen-containing pore formers such as phosphorus pentoxide are introduced into the carbon coating process, and the oxygen-containing pore former and the carbon coating layer undergo an oxidation reaction at high temperature to form dense and uniform macropores in the carbon coating layer, providing more channels for lithium ion embedding, while generating a larger specific surface area, and the lithium embedding active sites on the surface of the material are also increased accordingly, further improving the fast charging performance of the material.

[0074] According to some embodiments of the present invention, the temperature of the graphitization treatment in step S2 is 2600-3200°C.

[0075] According to some embodiments of the present invention, the temperature of the graphitization treatment in step S2 is 2800-3000°C.

[0076] According to some embodiments of the present invention, the time for graphitization treatment in step S2 is 2 to 6 hours.

[0077] According to some embodiments of the present invention, the time of graphitization treatment in step S2 is 3.5 to 4.5 hours.

[0078] According to some embodiments of the present invention, the time for graphitization treatment in step S2 is 4 hours.

[0079] According to the application of the third aspect of the embodiment of the present invention, a battery negative electrode material is provided, and the raw materials for preparing the negative electrode material include the above-mentioned graphite composite material.

[0080] According to the application of the third aspect of the embodiment of the present invention, a secondary battery is further provided. The secondary battery comprises the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned preparation method.

[0081] According to some embodiments of the present invention, the secondary battery is a lithium ion battery.

[0082] According to some embodiments of the present invention, the secondary battery further comprises a positive electrode material.

[0083] According to some embodiments of the present invention, raw materials for preparing the positive electrode material include a positive electrode active substance, a positive electrode conductor, and a positive electrode binder.

[0084] According to some embodiments of the present invention, the positive electrode active material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium nickel cobalt manganese oxide.

[0085] According to some embodiments of the present invention, the positive electrode conductive agent can be a conventional conductive agent, such as conductive carbon black (such as acetylene black, Super P, Super S, 350G or Ketjen black), conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes.

[0086] Conductive agents are used to ensure that the electrodes have good charge and discharge performance. A certain amount of conductive material is usually added during the production of the electrode sheet. It collects microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the electrodes and accelerate the movement rate of electrons. It can also effectively increase the migration rate of lithium ions in the electrode materials, thereby improving the charge and discharge efficiency of the electrodes. Conventional conductive agents in the field can be selected and added in conventional amounts without any restrictive provisions.

[0087] According to some embodiments of the present invention, the positive electrode binder may be a conventional binder, preferably a fluorine-based polymer and / or a synthetic rubber, and more preferably one or a combination of at least two of polyvinyl fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene, styrene-butadiene rubber, fluorine-based rubber or ethylene propylene diene rubber.

[0088] Typical but non-limiting examples of the combination include: a combination of polyvinyl fluoride and polyvinylidene fluoride, a combination of polytetrafluoroethylene and styrene-butadiene rubber-type rubber, a combination of styrene-butadiene rubber-type rubber, fluorine-based rubber and ethylene propylene diene rubber, a combination of polytetrafluoroethylene, styrene-butadiene rubber-type rubber and fluorine-based rubber, a combination of polyvinyl fluoride, polyvinylidene fluoride, polytetrafluoroethylene and styrene-butadiene rubber-type rubber, a combination of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber-type rubber, fluorine-based rubber and ethylene propylene diene rubber, etc., with polyvinylidene fluoride being particularly preferred.

[0089] According to some embodiments of the present invention, the raw materials for preparing the positive electrode plate include positive electrode active materials, positive electrode conductive agents and positive electrode binders in a mass ratio of (89-96): (1-4): (3-7). The positive electrode material of the lithium-ion battery contains a certain proportion of conductive agents and binders, which is conducive to the active material being well attached to the current collector when making the plate, thereby improving the charge and discharge efficiency of the positive electrode. It can be 89:1:3, 90:2:4, 92:3:5, 94:1.5:3.5, 94:1:3, 94:2:4, 95:1:3, 95:2:5 or 96:2:5, including but not limited to the listed values. At the same time, other values ​​not listed in the numerical range are also applicable.

[0090] According to some embodiments of the present invention, during the preparation process of the positive electrode material for lithium-ion batteries, the positive electrode active material, the positive electrode conductive agent and the positive electrode binder are prepared into a slurry with a solvent and coated on the positive electrode current collector. The surface density of the coating is 1.0 to 2.5 g / dm 2 . For example, 1.0g / dm 2 , 1.2g / dm 2 , 1.5g / dm 2 , 1.7g / dm 2 , 1.9g / dm 2 , 2.1g / dm 2 , 2.3g / dm 2 or 2.5g / dm 2 wait.

[0091] According to some embodiments of the present invention, the raw materials for preparing the negative electrode material further include a negative electrode binder and a negative electrode conductor.

[0092] According to some embodiments of the present invention, the negative electrode binder includes one or more of sodium alginate, lithium alginate, polyacrylic acid, sodium carboxymethyl cellulose or styrene-butadiene rubber, preferably sodium carboxymethyl cellulose or styrene-butadiene rubber. Conventional negative electrode binders can be used without particular limitation, and are only exemplary.

[0093] According to some embodiments of the present invention, the negative electrode conductive agent can be selected from conventional conductive agents, and typical but non-limiting conductive agents are, for example, conductive carbon black (such as acetylene black, Super P, Super S, 350G or Ketjen black), conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15 or Ks-6), carbon fiber or carbon nanotubes. The conductive agent is to ensure that the electrode has good charge and discharge performance. When the pole piece is made, a certain amount of conductive material is usually added to collect microcurrents between active materials and between active materials and current collectors to reduce the contact resistance of the electrode and accelerate the movement rate of electrons. At the same time, it can also effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode.

[0094] According to some embodiments of the present invention, the mass ratio of the negative electrode active material, the negative electrode conductive agent and the negative electrode binder is (89-96): (1-4): (3-7), which can be 89:1:3, 90:2:4, 92:3:5, 94:1.5:3.5, 94:1:3, 94:2:4, 95:1:3, 95:2:5 or 96:2:5, including but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The negative electrode material of the lithium ion battery contains a certain proportion of conductive agent and binder, which is conducive to the active material being well attached to the current collector when making the pole piece, thereby improving the charge and discharge efficiency of the negative electrode.

[0095] According to some embodiments of the present invention, during the preparation process of the negative electrode material for a lithium-ion battery, a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a solvent are prepared into a slurry, which is then coated on a negative electrode current collector.

[0096] According to some embodiments of the present invention, the surface density of the coating is 0.5 to 1.5 g / dm 2 . For example, 0.5g / dm 2 , 0.8g / dm 2 , 1.0g / dm 2 , 1.2g / dm 2 or 1.5g / dm 2 wait.

[0097] According to some embodiments of the present invention, the secondary battery also includes an isolation membrane, which can be selected from common commercially available isolation membranes, such as polyethylene (PE) isolation membranes, polypropylene (PP) isolation membranes, PE / PP composite isolation membranes, coated isolation membranes, aramid isolation membranes, etc.

[0098] According to some embodiments of the present invention, the secondary battery further comprises an electrolyte step, wherein the electrolyte contains a lithium salt.

[0099] According to some embodiments of the present invention, the lithium salt is preferably at least one of LiPF6, LiBF4, and LiTFSI. Any conventional lithium salt may be used. There is no particular limitation.

[0100] According to some embodiments of the present invention, the solvent of the electrolyte includes propylene carbonate, ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, N,N-dimethylacetamide, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, dimethoxymethane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfone, dimethyl ether, vinyl sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite or crown ether (12-crown-4) One or more.

[0101] According to some embodiments of the present invention, the solvent is a composite porous carbon layer raw material of ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0102] According to some embodiments of the present invention, the volume ratio of EC, DEC and EMC in the solvent is (25-45):(25-35):30.

[0103] According to some embodiments of the present invention, the volume ratio of EC, DEC and EMC in the solvent is (28-42):(28-32):30.

[0104] According to some embodiments of the present invention, the volume ratio of EC, DEC and EMC in the solvent is 1:1:1.

[0105] According to the application of the third aspect of the present invention, there is also provided an electrical device comprising the above-mentioned secondary battery.

[0106] According to a preferred embodiment of the present invention, the electrical device has at least the following beneficial effects: the secondary battery of the present invention has a higher energy density, can support higher energy output, and at the same time, can maintain good working performance even in cold environments, meeting the use requirements of electronic devices such as electric vehicles and smart phones in winter; the secondary battery of the present invention has good thermal stability and chemical stability, reducing the occurrence of safety accidents in the electrical device during the power consumption process.

[0107] According to some embodiments of the present invention, the electrical device is an electric vehicle, or other electrical devices such as energy storage systems, electric tools, drones, mobile devices such as wearable products, laptops, mobile phones, etc.

[0108] According to some embodiments of the present invention, the power-consuming device is an electric car or an electric bicycle, or other electric vehicles, such as an electric motorcycle, an electric scooter, an electric wheelchair, etc.

[0109] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0110] Figure 1 It is a schematic diagram of the structure of the graphite composite material in Example 1 of the present invention.

[0111] 1. Graphite; 2. Composite porous carbon layer; 21. Macropores. DETAILED DESCRIPTION

[0112] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0113] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0114] In the description of the present invention, if there are descriptions of "greater than", "less than", "exceeds", "lower than", etc., it is understood that the number is not included, and if there are descriptions of "above", "below", etc., it is understood that the number is included.

[0115] In the description of the present invention, if described with “between”, it means that the boundary value of the described range is included.

[0116] In the description of the present invention, "macropores" are pores larger than 50 nm.

[0117] In the description of the present invention, high-speed stirring is referred to as stirring speed of 1000-1500 rpm.

[0118] Traditional graphite negative electrode materials are highly crystalline graphite, with a graphite interlayer spacing of only 0.336nm, which does not support the rapid diffusion of lithium ions within graphite particles. In addition, due to the crystal characteristics of graphite itself, its surface has an anisotropic structure, and the active sites for lithium ion embedding are mainly distributed at the edges and defects of graphite sheets. There are fewer lithium embedding sites, and the charge transfer of lithium ions on the surface of the material is limited.

[0119] Among the modification methods to solve the problem of few active sites for lithium insertion on the graphite surface, amorphous carbon coating modification is a relatively common and effective means. Coating the graphite surface with amorphous carbon can increase the degree of isotropy of the graphite surface. In addition, amorphous carbon can also provide sufficient active sites for lithium insertion, which is conducive to the rapid charge transfer of lithium ions on the graphite surface. However, during the process of lithium insertion and deintercalation of the material, the amorphous carbon coating will also have more side reactions with the electrolyte, resulting in loss of active lithium in the battery and deterioration of the cycle performance.

[0120] In order to provide sufficient lithium insertion active sites, reduce the side reactions between the coating and the electrolyte, and improve the structural stability of the graphite particles, the present invention achieves this purpose by constructing a porous hard carbon composite graphitized carbon coating on the graphite surface. The hard carbon composite graphitized carbon coating provides sufficient lithium insertion active sites for the material on the graphite surface, while minimizing the side reactions between the material and the electrolyte, while stabilizing the graphite core structure and reducing the volume change of the graphite core during lithium insertion and deintercalation. On the other hand, the porous structure design of the coating can provide channels for lithium ions to quickly embed into the particles, which is beneficial to the rapid charging and discharging of the material.

[0121] In this structure, the pore structure of the coating layer affects the diffusion rate of lithium ions in the composite porous carbon layer coated graphite negative electrode material. The larger the pore size of the graphite, the faster the lithium ion diffusion rate, and correspondingly, the worse the cycle performance. This is attributed to the fact that the larger pore size provides a wider channel for lithium ions to embed into the graphite particles, while leading to a larger specific surface area, which accelerates the side reactions between the graphite particles and the electrolyte. The average pore size of the composite porous carbon layer coated graphite is above 15nm; in some embodiments of the present invention, the average pore size of the composite porous carbon layer coated graphite is 15 to 100nm, in some embodiments of the present invention, the average pore size of the composite porous carbon layer coated graphite is further controlled between 50 and 100nm, and in some embodiments of the present invention, the average pore size of the composite porous carbon layer coated graphite is further controlled between 70 and 90nm.

[0122] In some embodiments of the present invention, the specific surface area of ​​the composite porous carbon layer is 0.5 to 3.0 m2 / g, such as 0.5m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 2.6m 2 / g, 2.7m 2 / g, 2.8m 2 / g, 2.9m 2 / g or 3.0m 2 / g, etc. In some embodiments of the present invention, the specific surface area of ​​the composite porous carbon layer is 0.7 to 2.2 m 2 / g.

[0123] In the preparation process of the composite porous carbon layer coated graphite negative electrode material of the present invention, the pore size of the coating layer can be adjusted by adjusting the mixing ratio of oxygen-containing pore formers such as phosphorus pentoxide. In some embodiments of the present invention, the mixing ratio of the oxygen-containing pore former and the coating agent (i.e., the composite porous carbon layer raw material) is between 100:1 and 10:1. In some embodiments of the present invention, the mixing ratio of the oxygen-containing pore former and the coating agent is further controlled to be between 40:1 and 60:1. Specifically, in some embodiments of the present invention, the mixing ratio of the oxygen-containing pore former and the coating agent is further controlled to be 50:1.

[0124] In this structure, the thickness of the coating layer affects both the fast charging performance and the cycle performance of the composite porous carbon layer-coated graphite negative electrode material. When the coating layer is too thin, there are fewer active lithium insertion sites on the surface of the graphite material, and the fast charging performance is poor. When the coating layer is too thick, there are more side reactions between the graphite material and the electrolyte, and the cycle performance is poor. In some embodiments of the present invention, the thickness of the composite porous carbon layer is 20 to 200 nm. In some specific embodiments of the present invention, the thickness of the composite porous carbon layer is controlled between 50 and 150 nm. In some specific embodiments of the present invention, the thickness of the composite porous carbon layer is controlled between 50 and 80 nm. In addition, the ratio of graphitized carbon and hard carbon in the coating layer is also crucial. In some embodiments of the present invention, the mixing ratio of graphitized carbon precursors such as asphalt and hard carbon precursors in the coating layer of the present invention is 1:1 to 10:1. In some embodiments of the present invention, it is specifically controlled to be 5:1.

[0125] In another typical embodiment of the present invention, a method for preparing the above-mentioned graphite composite material is also provided, and the preparation method comprises the following steps:

[0126] Step 1: coating a composite porous carbon layer raw material containing a graphitized carbon precursor and a hard carbon precursor, graphite and an oxygen-containing pore-forming agent at high temperature in a coating machine, and the composite porous carbon layer raw material and the oxygen-containing pore-forming agent are melted and solidified on the surface of graphite particles to obtain pre-coated graphite;

[0127] Step 2, graphitizing the pre-coated graphite in step 1 at high temperature under an inert atmosphere to obtain a composite porous carbon layer-coated graphite material;

[0128] Among them, the ratio of the mass of graphite to the total mass of the composite porous carbon layer raw material is less than 28:1, the mass ratio of the graphitized carbon precursor to the hard carbon precursor is more than 1:1; the mass ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is more than 10:1.

[0129] Furthermore, the graphitized carbon precursor in step 1 may be asphalt, including one or more of coal tar asphalt, petroleum asphalt and natural asphalt.

[0130] Furthermore, the hard carbon precursor includes one or more of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose, and polyvinyl pyrrolidone.

[0131] Furthermore, the mixing ratio of the graphitized carbon precursor to the hard carbon precursor is 1:1 to 10:1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.

[0132] In some embodiments of the present invention, the mixing ratio of the graphitized carbon precursor to the hard carbon precursor is 5:1.

[0133] Step one also includes grinding and mixing the composite porous carbon layer raw material containing graphitized carbon precursor and hard carbon precursor in a high-speed shear mill to obtain a ground composite porous carbon layer raw material; through the grinding process, the two can be mixed more evenly and the coating effect is better.

[0134] Further, the rotation speed of the high speed shear mill is 10000rpm~30000rpm, such as 10000rpm, 11000rpm, 12000rpm, 13000rpm, 14000rpm, 15000rpm, 16000rpm, 17000rpm, 18000rpm, 19000rpm, 20000rpm, 22000rpm, 22000rpm, 23000rpm, 24000rpm, 25000rpm, 26000rpm, 27000rpm, 28000rpm, 29000rpm or 30000rpm, etc. For example, in some specific embodiments, the rotation speed of the high speed shear mill is 16000rpm.

[0135] Further, the ratio of the mass of graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 25:1. In some embodiments of the present invention, the ratio of the mass of graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 20:1, such as 5:1, 6:1, 7:1, 8:1, 9:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1. In some embodiments of the present invention, the mixing ratio of the mass of graphite to the composite porous carbon layer raw material is specifically 1:9. Adjusting the mixing ratio of the composite porous carbon layer raw material and graphite can change the coating thickness.

[0136] Further, in step 1, the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 10:1 to 100:1, such as 100:1, 95:1, 90:1, 85:1, 80:1, 75:1, 70:1, 65:1, 60:1, 55:1, 50:1, 45:1, 40:1, 35:1, 30:1, 25:1, 20:1, 15:1 or 10:1, etc. In some embodiments of the present invention, the mixing ratio of the composite porous carbon layer raw material and the oxygen-containing pore-forming agent is 50:1.

[0137] Furthermore, the coating machine in step one includes any one of a vertical kettle, a horizontal kettle, a drum furnace, and a melting machine.

[0138] Furthermore, in step 1, the high temperature coating temperature is 200-400°C, such as 200°C, 220°C, 250°C, 280°C, 300°C, 330°C, 350°C, 380°C or 400°C, etc. Preferably, it is 300-350°C.

[0139] Furthermore, in step 2, the high temperature graphitization time is 1 to 3 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, etc. Preferably, it is 2 hours.

[0140] Further, in step 2, the high temperature graphitization temperature is 2600-3200°C, such as 2600°C, 2650°C, 2700°C, 2750°C, 2800°C, 2850°C, 2900°C, 2950°C, 3000°C, 3050°C, 3100°C, 3150°C or 3200°C, etc. In some embodiments of the present invention, the high temperature graphitization temperature is 2800-3000°C.

[0141] Furthermore, in step 2, the high temperature graphitization time is 2 to 6 hours, such as 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, etc. In some embodiments of the present invention, in step 2, the high temperature graphitization time is 4 hours.

[0142] In another typical embodiment of the present invention, there is also provided the use of the above-mentioned graphite composite material in the preparation of negative electrode materials for secondary batteries such as lithium ion batteries and secondary batteries.

[0143] The present invention is further described in detail below through specific examples.

[0144] Example 1

[0145] This example provides a graphite composite material and its preparation method and application, such as Figure 1 As shown, the graphite composite material is composed of graphite 1 and a composite porous carbon layer 2 coated on the graphite 1, wherein the composite porous carbon layer 2 is composed of a composite of hard carbon and graphitized carbon, and the composite porous carbon layer contains a plurality of macropores 21. The specific preparation process is as follows:

[0146] Step 1: Grind coal tar pitch and phenolic resin in a high-speed shear mill at a mass ratio of 5:1 and mix at a speed of 16000 rpm for 30 minutes to obtain a composite porous carbon layer raw material; High-temperature coat the composite porous carbon layer raw material obtained by the above operation, graphite and phosphorus pentoxide in a mass ratio of 1:9:0.02 in a melting machine at 300°C for 2 hours to obtain pre-coated graphite;

[0147] Step 2: The pre-coated graphite obtained in step 1 is graphitized at 3000° C. for 4 h in an argon atmosphere to obtain a composite porous carbon layer-coated graphite negative electrode material.

[0148] This example also provides the use of the above graphite composite material in preparing a negative electrode material for a lithium ion battery and further uses the negative electrode material in preparing a lithium ion battery.

[0149] Specifically, the preparation process of the lithium-ion battery in this example includes the following steps:

[0150] (1) Preparation of positive electrode sheet:

[0151] The positive electrode active material nickel cobalt manganese (NCM523), the conductive agent carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 93:3:4, and the solvent N-methyl-2-pyrrolidone (NMP) is added, and the composite porous carbon layer raw materials are stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode current collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.

[0152] (2) Preparation of negative electrode sheet:

[0153] The graphite composite material, conductive carbon black, sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) emulsion prepared in the above steps are weighed in a mass ratio of 93:3:2:4, wherein the solid content of SBR in the SBR emulsion is 50%. The specific preparation method of the negative electrode slurry is: add deionized water, conductive carbon black and 70% CMC powder to a stirring tank, stir at low speed for 2 hours to form a conductive glue; add the graphite composite material to the conductive glue, stir at low viscosity and high speed for 1 hour to form a first mixed solution; add SBR emulsion to the first mixed solution, stir at high viscosity and high speed for 1 hour to form a second mixed solution; add ethanol and the remaining 30% CMC powder to the second mixed solution, stir at low viscosity and high speed for 2 hours to prepare the negative electrode slurry, and the volume ratio of deionized water to ethanol in the slurry is 9:1. The negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, dried in an oven, and then cold pressed and cut to obtain the negative electrode sheet.

[0154] (3) Preparation of electrolyte:

[0155] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.

[0156] (4) Preparation of isolation membrane

[0157] A commercially available polyethylene film was selected as the separator.

[0158] (5) Preparation of lithium-ion batteries

[0159] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through conventional processes such as vacuum packaging, standing, forming, and shaping.

[0160] Example 2

[0161] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0162] When preparing the graphite composite material, in step 1, the ratio of coal tar pitch to phenolic resin is 3:1.

[0163] The rest is exactly the same as in Example 1 and will not be described again here.

[0164] Example 3

[0165] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0166] When preparing the graphite composite material, in step 1, the ratio of coal tar pitch to phenolic resin is 4:1.

[0167] The rest is exactly the same as in Example 1 and will not be described again here.

[0168] Example 4

[0169] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0170] When preparing the graphite composite material, in step 1, the ratio of coal tar pitch to phenolic resin is 6:1.

[0171] The rest is exactly the same as in Example 1 and will not be described again here.

[0172] Example 5

[0173] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0174] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:7:0.02.

[0175] The rest is exactly the same as in Example 1 and will not be described again here.

[0176] Example 6

[0177] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0178] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:11:0.02.

[0179] The rest is exactly the same as in Example 1 and will not be described again here.

[0180] Example 7

[0181] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0182] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:13:0.02.

[0183] The rest is exactly the same as in Example 1 and will not be described again here.

[0184] Example 8

[0185] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0186] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:9:0.01.

[0187] The rest is exactly the same as in Example 1 and will not be described again here.

[0188] Example 9

[0189] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0190] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:9:0.04.

[0191] The rest is exactly the same as in Example 1 and will not be described again here.

[0192] Example 10

[0193] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0194] When preparing the graphite composite material, in step 1, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:9:0.06.

[0195] The rest is exactly the same as in Example 1 and will not be described again here.

[0196] Embodiment 11

[0197] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0198] When preparing the graphite composite material, in step 2, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:9:0.2.

[0199] The rest is exactly the same as in Example 1 and will not be described again here.

[0200] Example 12

[0201] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0202] When preparing the graphite composite material, in step 1, the ratio of coal tar pitch to phenolic resin is 20:1.

[0203] The rest is exactly the same as in Example 1 and will not be described again here.

[0204] Embodiment 13

[0205] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0206] When preparing the graphite composite material, in step 2, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:4:0.02.

[0207] The rest is exactly the same as in Example 1 and will not be described again here.

[0208] Comparative Example 1

[0209] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0210] When preparing the graphite composite material, in step 2, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:30:0.02.

[0211] The rest is exactly the same as in Example 1 and will not be described again here.

[0212] Comparative Example 2

[0213] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0214] When preparing the graphite composite material, in step 2, the ratio of the composite porous carbon layer raw material, graphite and phosphorus pentoxide is 1:9:0.005.

[0215] The rest is exactly the same as in Example 1 and will not be described again here.

[0216] Comparative Example 3

[0217] This example provides a graphite composite material and a preparation method and application thereof, which differs from Example 1 in that:

[0218] When preparing the graphite composite material, in step 1, the ratio of coal tar pitch to phenolic resin is 1:2.

[0219] The rest is exactly the same as in Example 1 and will not be described again here.

[0220] Test Case

[0221] In this example, the pore structure and distribution of the graphite composite material obtained in the embodiment and the comparative example were characterized by BET. The thickness of the composite porous carbon layer in the above embodiment was 50-150nm, and the porosity was between 2% and 9%. At the same time, the electrochemical performance of the lithium ion battery in the embodiment and the comparative example was tested. The details are as follows:

[0222] (1) Dynamic performance test: At 25°C, the lithium-ion battery prepared in the embodiment and the comparative example was fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium-ion battery was fully charged at a 4C rate, and then the negative electrode plate was disassembled and the lithium deposition on the surface of the negative electrode plate was observed. Among them, the area of ​​lithium deposition on the surface of the negative electrode plate is less than 5%, which is considered to be slight lithium deposition, the area of ​​lithium deposition on the surface of the negative electrode plate is 5% to 40%, which is considered to be moderate lithium deposition, and the area of ​​lithium deposition on the surface of the negative electrode plate is greater than 40%, which is considered to be severe lithium deposition, and it is judged to have poor fast charging performance.

[0223] (2) Cycle performance test: At 25° C., the lithium ion batteries prepared in the examples and comparative examples were charged at a 2C rate and discharged at a 1C rate to perform a full charge-discharge cycle test until the capacity of the lithium ion battery decayed to 80% of the initial capacity. The number of cycles was recorded. A cycle number less than 2000 was judged to be poor in cycle performance.

[0224] The characterization and test results are shown in Table 1 below.

[0225] Table 1

[0226]

[0227]

[0228] As can be seen from the above table, when the graphite composite material of the embodiment of the present invention is used to prepare the negative electrode material of the secondary battery, the serious lithium precipitation phenomenon of the prepared lithium-ion battery can be effectively avoided, and at the same time, the number of cycles can be guaranteed to be more than 2000 times. The thickness and average pore size of the coating layer have an important influence on the fast charging performance and cycle performance of the composite porous carbon layer coated graphite. When the quality of the coating raw material determines the thickness of the coating, when the quality of the coating raw material relative to the graphite kernel is too low, the thickness is too thin, the coating cannot completely cover the surface of the material, and a large part of the graphite surface is exposed, resulting in too few active sites on the surface of the material for lithium ion embedding, and the battery fast charging performance is poor. The kinetic performance test results of Comparative Example 1 are severe lithium precipitation. The average pore size of the coating layer affects the diffusion rate of lithium ions in the composite porous carbon layer coated graphite, and the average pore size can be controlled by adjusting the amount of oxygen-containing pore-forming agent phosphorus pentoxide added. The surface of the material with too small average pore size has fewer channels for lithium ion diffusion, the channel width is narrow, and the fast charging performance is poor. The kinetic performance test result of Comparative Example 2 is severe lithium precipitation. When the quality of the coating layer raw material is higher than that of the graphite core, the coating layer is thicker, the content of hard carbon and graphitized carbon in the material increases, and the incidence of side reactions between the material and the electrolyte increases. The lithium-ion battery prepared with this material as the negative electrode material loses relatively more active lithium during the long cycle process, and the cycle performance of the battery decreases. The material with a larger average pore size has a larger specific surface area, and the side reactions between the material and the electrolyte increase, and the cycle performance decreases.

[0229] In addition, the component ratio of the coating layer also has a certain influence on the performance. In the composite porous carbon layer, the ratio of graphitized carbon and hard carbon has a certain regulatory effect on the fast charging and cycle performance. When there is too little graphitized carbon and too much hard carbon, the side reactions between the material and the electrolyte increase. During a long cycle, excessive side reactions can easily lead to a rapid loss of active lithium in the battery, resulting in a significant decrease in the battery cycle performance. For example, the number of cycles in Comparative Example 3 is only 1764. When there is more graphitized carbon, the active sites on the surface of the graphite coated with the composite porous carbon layer are reduced for lithium ions to embed, the charge transfer rate of lithium ions on the surface of the particles is reduced, and the fast charging performance of the material is reduced.

[0230] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A graphite composite material, characterized in that: It includes graphite and a composite porous carbon layer coated on the graphite, wherein the composite porous carbon layer contains hard carbon and graphitized carbon, the raw materials for preparing the graphite composite material include composite porous carbon layer raw materials, graphite and oxygen-containing pore-forming agent, the composite porous carbon layer raw materials include hard carbon precursor and graphitized carbon precursor, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw materials is less than 28:1, the ratio of the mass of the graphitized carbon precursor to the hard carbon precursor is greater than 1:1; the ratio of the total mass of the composite porous carbon layer raw materials to the mass of the oxygen-containing pore-forming agent is greater than 10:

1.

2. The graphite composite material according to claim 1, characterized in that: The composite porous carbon layer satisfies at least one of the following parameters: 1) The composite porous carbon layer contains a plurality of macropores; 2) The average pore size of the composite porous carbon layer is 15 to 100 nm; 2) The specific surface area of ​​the composite porous carbon layer is 0.5 to 3.0 m 2 / g; 3) the porosity of the composite porous carbon layer is above 2%; 4) the thickness of the composite porous carbon layer is 20 to 200 nm.

3. The graphite composite material according to claim 1, characterized in that: The preparation raw materials meet at least one of the following parameters: 1) The mass ratio of the graphitized carbon precursor to the hard carbon precursor is 1:1 to 10:1; 2) The ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 25:1; 3) The ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 10:1 to 100:1; 4) The hard carbon precursor includes at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose, and polyvinyl pyrrolidone; 5) The graphitized carbon precursor includes at least one of coal tar pitch, petroleum pitch and natural pitch; 6) The oxygen-containing pore-forming agent includes phosphorus pentoxide.

4. A method for preparing a graphite composite material, characterized in that: The steps include: S1, mixing the composite porous carbon layer raw material with graphite and an oxygen-containing pore-forming agent, and heating them to obtain pre-coated graphite; S2, graphitizing the pre-coated graphite under an inert atmosphere to obtain the graphite composite material; Among them, the composite porous carbon layer raw material includes a hard carbon precursor and a graphitized carbon precursor, the ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is less than 28:1, and the mass ratio of the graphitized carbon precursor to the hard carbon precursor is greater than 1:1; the ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is greater than 10:

1.

5. The preparation method according to claim 4, characterized in that: The preparation method comprises at least one of the following conditions: 1) The temperature is 200-400° C., and / or the pre-coating treatment time is 1-3 hours; 2) The temperature of the graphitization treatment in step S2 is 2600-3200° C., and / or the graphitization treatment time in step S2 is 2-6 hours.

6. The preparation method according to claim 4, characterized in that: The step S1 also includes the step of subjecting the composite porous carbon layer raw material containing the hard carbon precursor and the graphitized carbon precursor to high-speed shearing and grinding treatment.

7. The preparation method according to claim 4, characterized in that: The raw materials used in the preparation method meet at least one of the following characteristics: 1) The mass ratio of the graphitized carbon precursor to the hard carbon precursor is 1:1 to 10:1; 2) The ratio of the mass of the graphite to the total mass of the composite porous carbon layer raw material is 5:1 to 25:1; 3) The ratio of the total mass of the composite porous carbon layer raw material to the mass of the oxygen-containing pore-forming agent is 10:1 to 100:1; 4) The hard carbon precursor includes at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose, and polyvinyl pyrrolidone; 5) The graphitized carbon precursor includes at least one of coal tar pitch, petroleum pitch and natural pitch; 6) The oxygen-containing pore-forming agent includes phosphorus pentoxide.

8. A battery negative electrode material, characterized in that: The raw material for preparing the negative electrode material includes the graphite composite material as described in any one of claims 1 to 3 or includes the graphite composite material prepared by the preparation method as described in any one of claims 4 to 7.

9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode material as claimed in claim 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Nitrogen-doped carbon-coated graphite negative electrode material, preparation method and application thereof, and battery

    CN117393737A